Advances in Modeling Interactions Between Sea Ice and Ocean Surface Waves - Roach, Lettie A.; Bitz, Cecilia M.; Horvat, Christopher; Dean, Samuel M. (Journal of advances in modeling earth systems, 2019)
Recent field programs have highlighted the importance of the composite nature of the sea ice mosaic to the climate system. Accordingly, we previously developed a process‐based prognostic model that captures key characteristics of the sea ice floe size distribution and its evolution subject to melting, freezing, new ice formation, welding, and fracture by ocean surface waves. Here we build upon this earlier work, demonstrating a new coupling between the sea ice model and ocean surface waves and a new physically based parameterization for new ice formation in open water. The experiments presented here are the first to include two‐way interactions between prognostically evolving waves and sea ice on a global domain. The simulated area‐average floe perimeter has a similar magnitude to existing observations in the Arctic and exhibits plausible spatial variability. During the melt season, wave fracture is the dominant FSD process driving changes in floe perimeter per unit sea ice area—the quantity that determines the concentration change due to lateral melt—highlighting the importance of wave‐ice interactions for marginal ice zone thermodynamics. We additionally interpret the results to target spatial scales and processes for which floe size observations can most effectively improve model fidelity. Plain Language Summary In the outer margins of polar sea ice cover, complex interactions occur between sea ice and ocean surface waves. Waves travel through sea ice with properties of in‐ice waves dependent on the size of sea ice floes, which are discrete pieces of sea ice. Sea ice may be fractured by waves, and waves determine the type of sea ice formation that occurs. This study presents advances in numerical modeling of these processes, including communication between a sea ice model and a wave model. We investigate how different physical processes determine the perimeter of sea ice floes exposed to the ocean. This in turn determines the amount of melt that occurs at the edge of sea ice floes. Key Points A new global prognostic coupled ocean surface wave‐sea ice model has important climate feedbacks Sea ice forms as either pancake or nilas depending on stress exerted by ocean surface waves Wave‐related processes drive variability in floe perimeter and therefore determine lateral melt